Financial ratios as early indicators of business failure: evidence from Serbia - Denis Kušter (Anali Ekonomskog fakulteta u Subotici, 2023)
The problem of corporate bankruptcies has intrigued the scientific community for years due to its practical significance. There is no country whose economic well-being is not affected by business failures. The research problem stems from the lack of analyzes related to issue of business failures in the the Republic of Serbia. The main aim of the research paper is to determine whether ratio indicators are relevant in predicting business failure one, two and three years before bankruptcy proceedings start. The research was conducted on a sample of 100 companies from the Republic of Serbia teritorry. The data for ratios calculation was  taken from the official website of the Business Registers Agency. Statistical analysis is based on Mann-Whitney test that is used to identify differences between two groups with respect to a variable (ratio). The test was conducted in SPSS v.26 tool. Results of the research indicate that financial ratios can be useful for business failure prediction even three years before bankruptcy proceedings start, since there are statistically significant differences in ratio values between bankrupted and solvent companies.